PERBEDAAN HASIL BELAJAR MATA KULIAH KONSTRUKSI GAMBAR BANGUNAN MAHASISWA JURUSAN TEKNIK SIPIL FT-UNP BERDASARKAN SEKOLAH ASAL - 712-721 , Hafero Pumicia (Universitas Negeri Padang, 2015)
ABSTRACT From the data obtained UNP Puskom the large number of high school graduates from the vocational school students graduate on Course Construction of Image Building seen that vocational graduates can better understand the material provided lecturers, compared to high school graduates. Because, students who graduated from vocational already have previous experience the lecture begins, meaning that students who do not understand the material can be triggered to be more creative. The purpose of this study was to reveal the differences in learning outcomes of the course students Image Building Construction Department of Civil Engineering FT-UNP based school of origin. This type of research is the study of ex-post facto. The population in this study were all students of class of 2013 and 2014 Department of Civil Engineering D3 and S1 are taking courses totaling Image Building Construction 279 students, while samples in this study were as many as 164 students. Data analysis techniques in this study is the normality test, homogeneity test and test hypotheses. Results of the data analysis and hypothesis testing has been conducted, proving that there are differences in learning outcomes of the course students Image Building Construction Department of Civil Engineering FT-UNP based school of origin. Because, 0009 Asymp.Sig value <0.05 means that there are differences in learning outcomes of students in courses based Image Building Construction of the school of origin. Judging from the average student results based on home-school learning outcomes of students from vocational higher when compared to the learning outcomes of students from high school. Keywords: Hasil Belajar, Sekolah Asal